PASAR KERAJINAN TANGAN DENGAN PENDEKATAN ARSITEKTUR METAFORA DI KLATEN - Febrina Kusumandari; Bambang Triratma; Muhammad Asrori (ARSITEKTURA, 2015)
There are some reasons in building Handicraft Market in Klaten. The reasons are; there are so many handicraft potentials around Klaten, unavailable places which can provide all of the handicraft potentials in Klaten, and government’s plan in developing facilities in Klaten. However, many young people start to leave and forget this heritage that should be protected. The problem that appears is how to design the facilities that can support and develop vacation industry in Klaten that consist of trading activity, giving information and promoting handicraft, and also recreation place. Therefore, it can make Klaten knowing by people. The method that is used in designing the market is architecture metaphor. The shape and meaning that is applied into the design is taken from Juwiring umbrella. The result is design of a Handicraft Market in Klaten which can provide place for trading activity, giving information and promoting handicraft, and recreation which its design and building adopts from Juwiring umbrella’s shape. Juwiring umbrella is one of Klaten special handicrafts, so the expression of building reflects the activity inside the market. Then, Juwiring umbrella can preserve its existence and become Klaten’s icon. Keywords: Market, Handicraft, Architecture Metaphor, Juwiring umbrella